Corn (Zea mais L.) sowing quality in the province of Corrientes, Argentina - Pozzolo, Oscar Ruben; Hidalgo, Ramón Jesús; Domínguez, José Fabio; Giménez, Laura (Facultad de Ciencias Agrarias, Universidad Nacional de Cuyo, 2020)
In three departments of the Corrientes province, the performance of 6 seeders was evaluated during corn sowing at three different speeds for each machine. A randomized complete block design was used with nested treatments arrangement. A seeder factor (6 types), a speed factor (3 levels) and three blocks determined a total of 54 experimental units. As for the speed factor, the first level corresponds to speed 2 (Sp 2) which the operator regularly uses. The second level and the third level correspond to a lower speed (Sp 1) and a higher speed (Sp 3) respectively which were used for this study. The equidistance between seeds and sowing depth were analysed as the response variable. Conclusions: 1) Four of the six seeders studied at three chosen speeds showed no differences regarding seed deposition. This was observed considering significant differences between sowing depth and seed spacing in a given line. 2) The two methodologies used to evaluate sowing efficiency, i.e. the coefficient of variation (CV) and the ISO 7256-1 standard, showed differences in evaluation. The second technique was more accurate since no differences between treatments were found with the CV. 3) According to these results, it is possible to conclude that the corn sowing quality in the Corrientes province is acceptable at the sowing speeds used by the contractors.